A high-precision laser quenching method for a threaded joint and a threaded joint
By precisely matching the shape, size, and angle of the laser spot, and combining the laser power and scanning speed, the problems of uneven hardened layer and poor adaptability to working conditions in existing threaded joints have been solved, achieving high-precision laser hardening of threaded joints and improving the comprehensive mechanical properties and service life of threaded joints.
Patent Information
- Application Number
- CN202611132213.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-08-25
AI Technical Summary
Existing laser hardening processes have problems such as uneven hardened layer thickness, low matching degree between laser spot and tooth profile, and poor adaptability to working conditions on threaded joints, which makes the threaded connection prone to failure and cannot meet the needs of different drilling conditions.
Based on the application scenario, tooth profile parameters, and material properties of the threaded joint, the shape, size, and irradiation angle of the laser spot are precisely matched, and high-precision scanning quenching of the guide side and the load-bearing side of the threaded joint is achieved by controlling the laser power and scanning speed.
It improves the optimal matching between the stress field of the quenched layer and the service load, significantly enhances the wear resistance and fatigue resistance of the threaded joint, and ensures safe and reliable operation under complex downhole conditions.
Smart Images

Figure CN122629294A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of laser quenching technology, specifically relating to a high-precision laser quenching method for threaded joints and the threaded joint itself. Background Technology
[0002] In oil drilling downhole tools, drill pipe accounts for more than 80% of the tubing string length and is a key component for transmitting power and delivering drilling fluid. The tubing string needs to withstand combined stresses such as tension, compression, bending, internal pressure, external pressure, and thermal cycling for extended periods in different well sections. Drill pipes are connected by threads to form the tubing string, and the threaded connection is a critical stress-bearing area. Statistics show that more than 80% of tubing string failures occur at threaded connections. The performance of the threads directly affects the drilling rig's efficiency and safety, and thread failure often begins with thread sticking.
[0003] To prevent thread sticking, current API standards recommend copper plating or phosphating the thread surface and applying thread grease. However, this treatment does not fundamentally solve the problem of thread sticking and has drawbacks such as serious environmental pollution and gradual phasing out due to environmental restrictions. To improve the wear resistance of the thread surface, the industry has also tried nitriding and coating technologies, but the hardness difference between the hardened layer and the substrate after nitriding is too large and it is prone to deformation and cracking, while coating technology is expensive and its effectiveness is uncertain.
[0004] In recent years, laser hardening technology has been increasingly applied to the surface hardening of threads in the oil pipe industry due to its advantages such as high efficiency, energy saving, and minimal deformation. Laser hardening utilizes a high-energy-density laser beam to scan the workpiece surface, rapidly austenitizing the material and then subjecting it to self-excited cooling and hardening. However, despite the theoretical advantages of laser hardening, existing thread laser hardening processes still suffer from significant deficiencies in precision control and parameter matching during actual industrial production. This results in uneven hardened layer quality, making it difficult to meet the demands of various complex drilling conditions. First, the low matching degree between the laser spot energy distribution and size and the thread profile leads to uneven hardened layer thickness on a single thread, posing safety hazards. Existing laser hardening processes often lack a precise matching mechanism for the thread flank geometry when selecting the laser spot. On one hand, the energy distribution of traditional laser spots is usually uneven, resulting in significant differences in heat input between the center and edge of the scanning trajectory. After hardening, an unevenly thick hardened layer forms on the thread flank surface. Under thread stress, the shallower areas are prone to wear failure first, while the deeper areas may coarsen due to excessive heat input, failing to provide uniform and stable wear-resistant support across the entire flank surface. On the other hand, the selection of the laser spot size is largely based on experience. If the spot size is too large, laser energy easily overflows to the thread root arc area, causing the formation of a hard and brittle structure at the root, which is highly susceptible to becoming a crack source under alternating loads, leading to joint fracture. If the spot size is too small, it cannot completely cover the contact working surface of the thread flank, and the unhardened areas will wear first, reducing the overall hardening effect. Furthermore, different drilling environments place varying performance requirements on drill pipes. For instance, low-wear scenarios (such as vertical wells and cluster wells) require extremely high process stability and a uniform wear-resistant layer, while high-wear scenarios (such as horizontal wells and extended reach wells) demand extremely high resistance to severe wear and fatigue. Existing laser hardening processes typically employ a one-size-fits-all parameter setting, failing to differentiate adjustments based on specific working conditions and laser spot characteristics. This results in products that cannot optimally match the specific downhole service environment, limiting the widespread application of laser hardening technology in high-end drill pipe joints.
[0005] Secondly, the fixed laser irradiation angle and lack of scenario-specific adaptation of process parameters result in low energy absorption efficiency and poor adaptability to operating conditions. Drill pipe joint threads have a taper and variable tooth flank angles (typically different on the guide and bearing sides). Existing laser hardening equipment typically uses a fixed irradiation angle for scanning, failing to consider the impact of thread geometry on laser absorption rate and shielding effects. A fixed angle may cause laser beam obstruction at the root of the bearing side, creating a hardening blind zone, or an excessively large incident angle may increase energy reflectivity, resulting in insufficient actual energy absorption. This, in turn, leads to uneven distribution of the hardened layer thickness along the tooth flank height, affecting the accuracy and stability of the thread fit.
[0006] Therefore, developing a high-precision laser quenching method for threaded joints that can precisely control the shape and size of the laser spot, optimize the irradiation angle, and adapt to different working conditions has become an urgent technical problem for those skilled in the art to solve, in order to address the current problems of rough process control, uneven hardened layer thickness, and poor adaptability of products to working conditions.
[0007] It should be noted that this part of the present invention only provides background technology related to the present invention, and does not necessarily constitute prior art or known technology. Summary of the Invention
[0008] This invention provides a high-precision laser quenching method for threaded joints and a threaded joint, which at least solves the technical problems of low laser quenching precision of existing threaded joints, resulting in uneven thickness of the hardened layer on a single tooth, low matching degree between the laser spot and the tooth profile, posing safety hazards, and the inability of the resulting products to meet the needs of different drilling conditions.
[0009] To achieve the above objectives, in a first aspect, the present invention provides a high-precision laser quenching method for threaded joints, comprising the following steps: The shape of the laser spot is determined based on the application scenario of the threaded joint; Based on the thread profile parameters of the threaded connector, determine the size of the laser spot and the irradiation angle of the laser beam; The laser power and scanning speed for laser quenching are determined based on the properties of the joint material. Using the determined laser spot, irradiation angle, laser power, and scanning speed, the laser beam is used to scan and quench the guide side and load-bearing side of the threaded joint to form a hardened layer.
[0010] Preferably, the application scenarios of the threaded joint include low-wear scenarios and high-wear scenarios; if the application scenario is a low-wear scenario, the laser spot is determined to be a flat-topped circular spot; if the application scenario is a high-wear scenario, the laser spot is determined to be a rectangular spot.
[0011] Preferably, determining the size of the laser spot specifically includes: Calculate the linear length of the bearing side of the thread tooth based on the thread profile parameters of the threaded joint; When the laser spot is determined to be a flat-topped circular spot, the diameter of the flat-topped circular spot is 85% to 115% of the linear length on the bearing side; Alternatively, when the laser spot is determined to be a rectangular spot, the width of the rectangular spot is 85% to 115% of the linear length of the bearing side.
[0012] Preferably, determining the illumination angle of the laser beam includes: The angle between the central axis of the laser beam and the axis of the threaded joint is determined to be 30°~70°; The illumination angle includes the guide side illumination angle and the load-bearing side illumination angle, which are determined independently.
[0013] Preferably, both the irradiation angle on the bearing side and the irradiation angle on the guide side are the angles between the laser beam and the axis of the threaded joint; The formula for calculating the irradiation angle on the bearing side is:
[0014] in, For the irradiation angle on the bearing side, The linear length of the thread tooth on the bearing side. The radius of the tooth root arc, It is a tooth-shaped half-angle; The formula for calculating the guide side illumination angle is:
[0015] in, For the guide side illumination angle, The linear length of the thread guide side. The radius of the tooth root arc, It is a tooth-shaped half-angle.
[0016] Preferably, the formula for calculating the linear length of the thread tooth bearing side is:
[0017] in, The linear length of the thread tooth on the bearing side. The height of the tooth profile. The radius of the tooth root arc, The taper of the threaded connector. It is a tooth-shaped half-angle.
[0018] Preferably, the formula for calculating the linear length of the thread guide side is:
[0019] in, The linear length of the thread guide side. The height of the tooth profile. The radius of the tooth root arc, The taper of the threaded connector. It is a tooth-shaped half-angle.
[0020] Preferably, the guide side illumination angle and the load-bearing side illumination angle are also independently compensated, with the angle compensation range being 0°~10°.
[0021] Preferably, the laser power and scanning speed for laser quenching are determined based on the properties of the joint material, including: When the connector material is medium carbon alloy steel, the laser power is 300W~2000W and the scanning speed is 10mm / s~60mm / s; When the connector material is aluminum alloy, the laser power is 300W~1000W and the scanning speed is 2mm / s~10mm / s.
[0022] Preferably, the laser power and scanning speed satisfy the following energy density relationship:
[0023] in, The critical energy density of the joint material is 15 J / mm². 2 ~60J / mm 2 ; Laser power; For scanning speed; It represents the diameter of a flat-topped circular light spot or the width of a rectangular light spot.
[0024] Preferably, a laser beam is used to scan and quench the guide side and the load-bearing side of the threaded joint, specifically including: First, laser hardening scanning is performed on the guide side of the threaded joint; After completing the quenching scan on the guide side, the bearing side of the threaded joint is then subjected to laser quenching scan. In the laser quenching process, the scanning direction is always from the large end to the small end of the threaded joint, where the laser beam moves to scan.
[0025] Secondly, the present invention provides a threaded joint that has been treated by the laser hardening method of the first aspect.
[0026] The beneficial effects of this invention are as follows: This invention, based on the actual application scenarios of threaded joints, customizes the laser spot type to achieve optimal matching between the stress field of the quenched layer and the service load. Existing laser quenching processes typically use a fixed spot type to process all joints, which cannot take into account the complex and ever-changing downhole conditions.
[0027] This invention targets low-wear scenarios (such as vertical wells and cluster wells, with normal threading frequency and minimal thread wear). It utilizes a flat-topped circular laser spot, ensuring uniform energy distribution within the spot area. This results in a more uniform temperature field across the entire heating zone, eliminating energy spikes and significantly reducing the risk of localized melting. Within the spot's coverage area, energy deposition along the depth direction is uniform, with each hardened layer exhibiting a flat, inverted trapezoidal or basin-shaped cross-section, minimal depth fluctuations, and highly consistent hardness and microstructure across the entire treated area. Due to the uniform energy distribution, the flat-topped laser spot is less sensitive to process parameters, providing a wider process window and higher robustness. As long as the average energy density remains within a safe range, the entire spot area remains in a safe heating state, exhibiting higher tolerance for equipment and parameter fluctuations and better process reproducibility.
[0028] For high-wear scenarios (such as horizontal wells, extended reach wells, and ultra-deep wells, where torque levels are extremely high and fluctuate dramatically, and the frequency of thread engagement and disengagement is also high, leading to significant thread wear), a rectangular laser spot is selected. Utilizing its linear synchronous heating, the heat input is completely synchronized in the height direction, resulting in a highly uniform hardened layer depth. This produces a uniformly deep hardened layer on the thread flank, with a consistent microstructure across the entire flank, eliminating weak points. The resulting symmetrical residual compressive stress field effectively inhibits the initiation and propagation of fatigue cracks, significantly improving impact and fatigue resistance. Uniform and synchronous energy injection ensures that the process effect closely matches theoretical calculations, and the parameters are easily transferable and reproducible.
[0029] This invention effectively solves the problem of uneven hardened layer quality caused by rough control of the laser quenching area in existing technologies by matching the laser spot size according to the thread profile parameters. Preferably, this invention controls the spot size to 85%~115% of the linear length of the bearing side. This targeted size design ensures that the laser energy accurately covers the working surface of the thread tooth side. By precisely matching the spot size, this invention not only ensures comprehensive strengthening of the tooth side surface but also effectively avoids the stress concentration area at the tooth root, significantly reducing the safety hazard of joint fracture and improving the accuracy and stability of the thread fit.
[0030] Furthermore, this invention preferably calculates the laser beam irradiation angle precisely using theoretical formulas and combines this with the matching of the spot size and thread profile parameters to achieve high-precision control of the quenching zone. Drill pipe joint threads have a taper and variable tooth flank angles; existing fixed-angle scanning methods are prone to creating blind spots or energy reflection losses. This invention calculates the optimal irradiation angle based on the thread profile half-angle, taper, and root radius, ensuring that the laser beam can act perpendicularly or nearly perpendicularly on the thread flank surface, avoiding quenching blind spots caused by geometric obstruction.
[0031] Preferably, this invention also precisely controls the laser power and scanning speed through the critical energy density relationship, achieving a match between process parameters and material physical properties. By controlling the laser power and scanning speed according to the critical energy density range of different materials, this invention ensures that the material surface reaches the austenitizing temperature without melting or burning, avoiding quenching failures caused by empirically set parameters in existing technologies. Preferably, for different materials such as medium carbon alloy steel and aluminum alloys, this invention provides corresponding power and speed windows, enabling the resulting products to be optimally matched to specific downhole service environments, achieving an ideal balance of wear resistance and toughness in both low-wear and high-wear scenarios.
[0032] More preferably, this invention employs a scanning quenching sequence of first the guide side and then the load-bearing side, utilizing the laser heat conduction effect to achieve precise control of the microstructure. During load-bearing side quenching, the heat generated by the laser is conducted to the already quenched guide side, effectively performing a self-tempering treatment on the guide side. This process sequence effectively improves the toughness of the guide side, eliminates some quenching stress, and avoids performance degradation caused by localized tempering on the load-bearing side. Combined with a scanning direction from the large end to the small end, it ensures the stability and consistency of the quenching process, further enhancing the overall mechanical properties of the threaded joint.
[0033] Finally, the laser quenching process used in this invention eliminates the need for traditional quenching media, minimizes the heat-affected zone and workpiece deformation, and achieves high-quality surface treatment through precise control of laser parameters, facilitating automated production. Compared to traditional copper plating or phosphating, this invention significantly improves the hardness and wear resistance of the threaded surface while avoiding environmental pollution, meeting the requirements of green manufacturing. Furthermore, by controlling the laser spot shape to adapt to different working conditions, the joint possesses both high wear resistance and excellent impact toughness, ensuring the safe and reliable operation of the drill pipe joint under complex downhole conditions. Attached Figure Description
[0034] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0035] Figure 1 This is a schematic diagram of the structure of the laser-quenched region for external threads provided in an embodiment of the present invention; Figure 2 This is a schematic diagram of the structure of the laser-quenched internal thread region provided in an embodiment of the present invention; Figure 3 This is a schematic diagram of the thread profile provided in an embodiment of the present invention; Figure 4 This is a schematic diagram of the structure of laser quenching on the external thread guide side provided in an embodiment of the present invention; Figure 5 This is a schematic diagram of the structure of laser quenching on the bearing side of the external thread provided in an embodiment of the present invention; Figure 6 A partially enlarged structural diagram of laser quenching on the external thread guide side and the load-bearing side provided in an embodiment of the present invention; Figure 7 This is a schematic diagram of the structure of laser quenching on the guide side of the internal thread provided in an embodiment of the present invention; Figure 8This is a schematic diagram of the structure of laser quenching on the bearing side of the internal thread provided in an embodiment of the present invention; Figure 9 This is a schematic diagram of the thread profile parameters of the threaded connector provided in an embodiment of the present invention; Figure 10 An optical microscope image of the hardened layer on the bearing side of the threaded joint provided in Embodiment 1 of the present invention; Figure 11 An optical microscope image of the hardened layer on the bearing side of the threaded joint provided in Comparative Example 1 of the present invention.
[0036] Explanation of reference numerals in the attached figures: 1. External thread; 2. Quenched thread area of external thread; 3. Thread axis; 4. Internal thread; 5. Quenched thread area of internal thread; 6. Thread bearing flank; 7. Thread crest; 8. Thread root arc; 9. Thread guide flank; 10. Thread taper line; 11. External thread laser; 12. Quenching laser beam; 13. Internal thread laser. Detailed Implementation
[0037] In this invention, unless otherwise stated, directional terms such as "up," "down," "left," and "right" are generally understood in conjunction with the accompanying drawings and the directions shown in actual applications.
[0038] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this invention, "a plurality of" means two or more, unless otherwise explicitly specified.
[0039] In this invention, unless otherwise explicitly specified and limited, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" of the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.
[0040] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. The terms "optional" and "discretionary" mean that they may or may not be included (or may or may not be present).
[0041] To achieve the above objectives, in a first aspect, the present invention provides a high-precision laser quenching method for threaded joints, comprising the following steps: The shape of the laser spot is determined based on the application scenario of the threaded joint; Based on the thread profile parameters of the threaded connector, determine the size of the laser spot and the irradiation angle of the laser beam; The laser power and scanning speed for laser quenching are determined based on the properties of the joint material. Using the determined laser spot, irradiation angle, laser power, and scanning speed, the laser beam is used to scan and quench the guide side and load-bearing side of the threaded joint to form a hardened layer.
[0042] The high-precision laser quenching method for threaded joints provided by this invention is based on the elimination of the fixed process parameter mode in existing technologies. Instead, it uses multi-dimensional parameter matching based on the application scenario, tooth profile geometry, and material properties. In existing technologies, laser quenching processes often ignore the subtle geometric differences in thread profiles and the complexity of downhole working conditions. They typically use a single spot shape and fixed power and speed to process all types of joints, resulting in uneven hardened layer thickness, low spot-to-tooth profile matching, and even the safety hazard of tooth root cracking. This invention first determines the scene-matched spot shape, then accurately calculates the spot size and irradiation angle based on tooth profile parameters, and finally determines the power and speed based on the material's critical energy density, forming a complete high-precision process control logic. This step-by-step determination method ensures that the laser energy can accurately cover the working surface of the thread tooth side while avoiding the stress-concentrated tooth root arc region, achieving the optimal match between wear resistance and toughness.
[0043] Understandably, determining the laser spot shape based on the application scenario of the threaded joint is a targeted design based on the differences in thread failure mechanisms under different working conditions. The failure modes of threaded joints are mainly divided into wear failure and fracture failure, each corresponding to different load-bearing characteristics. For working conditions mainly subjected to contact stress, wear is the primary failure mode. In this case, a laser spot shape with concentrated energy distribution and clear edge cutoff needs to be selected to obtain a high-hardness structure and resist fretting wear. Conversely, for working conditions mainly subjected to impact loads, toughness is key to preventing brittle fracture. In this case, a laser spot shape with uniform energy distribution needs to be selected to obtain a more balanced toughness structure and better impact resistance. If a uniformly distributed laser spot is incorrectly selected in a heavy-load scenario, it may lead to insufficient surface hardness and decreased wear resistance; if a concentrated laser spot is incorrectly selected in an impact scenario, it may lead to slightly lower toughness and insufficient fatigue resistance. Therefore, this application selects the laser spot according to the scenario to ensure the reliability of the joint in specific service environments.
[0044] Understandably, determining the laser spot size and laser beam irradiation angle based on the thread profile parameters of the threaded joint is to address the uneven energy distribution and shielding issues caused by the thread geometry. The linear length of the bearing surface on the thread flank is a fixed geometric parameter, and the choice of spot size directly determines the coverage area of the quenching zone. This invention controls the spot size based on the thread profile parameters. This targeted size design ensures that the laser energy accurately covers the working surface of the thread flank. If the spot size is too small, it cannot completely cover the contact working surface, and the unquenched area will wear first, reducing the overall quenching effect. Furthermore, stress concentration is prone to occur at the boundary between the unquenched and quenched areas. If the spot size is too large, the laser energy is prone to overflow to the thread root arc area, leading to the formation of a hard and brittle martensitic structure at the thread root. The thread root is the area with the highest stress concentration coefficient. After tightening, the local stress level can reach the material yield strength. Once a hard and brittle phase exists at the thread root, it is very easy to become a crack initiation under alternating loads, causing the joint to fracture. Therefore, by precisely matching the spot size based on tooth profile parameters, the overall reinforcement of the tooth lateral surface is ensured, while the stress concentration area at the tooth base is effectively avoided, significantly reducing the safety hazard of joint fracture.
[0045] Furthermore, the laser beam irradiation angle also needs to be determined independently based on the thread profile parameters. Drill pipe joint threads have a taper and variable flank angles. Existing fixed-angle scanning methods easily lead to laser beam obstruction at the root on the bearing side or increased energy reflectivity due to excessive incident angles. This invention calculates the optimal irradiation angle based on the thread profile parameters of the threaded joint, ensuring that the laser beam can act perpendicularly or nearly perpendicularly on the thread flank surface. If the irradiation angle is too small, the laser beam may be obstructed by adjacent thread teeth, failing to effectively irradiate the root on the bearing or guide side, forming a quenching blind zone and resulting in insufficient hardened layer thickness at the flank root. If the irradiation angle is too large, the excessive incident angle reduces energy absorption efficiency, with most energy being reflected, and may cause the laser spot to be elongated on the flank surface, resulting in uneven energy density distribution and affecting quenching uniformity. Therefore, determining the irradiation angle based on the thread profile parameters avoids quenching blind zones caused by geometric obstruction, ensures uniform distribution of hardened layer thickness along the flank height direction, and simultaneously improves the laser energy absorption rate.
[0046] Understandably, determining the laser power and scanning speed for laser quenching based on the properties of the joint material is an adaptation based on the differences in the thermophysical properties of the materials. Different materials have different properties; for example, the thermal conductivity of different joint materials varies greatly, and heat is rapidly conducted to the substrate during laser heating. Therefore, this invention uses material properties to deduce the laser power and scanning speed. If the power is too low or the speed is too high, the energy input is insufficient, and the material surface cannot reach the austenitizing temperature, thus failing to form martensite. If the power is too high or the speed is too slow, the energy input is excessive, which may lead to melting, burning, or quenching cracks on the material surface. By determining the power and speed based on material properties, the quenching failure caused by setting parameters based on experience in the prior art is avoided, ensuring that the energy density always falls within the effective quenching range, so that the resulting product can be optimally matched to the specific downhole service environment.
[0047] In summary, the method provided by this invention has a close logical connection between its steps. The scene determines the shape of the laser spot, thus affecting the microstructure type; the tooth profile determines the size and angle of the laser spot, thus affecting the accuracy and safety of the quenching zone; the material determines the power and speed, thus affecting the thickness and effectiveness of the hardened layer. Any equivalent step adjustments based on this logic fall within the protection scope of this invention. This invention effectively solves the problem of uneven hardened layer quality caused by rough control of the laser quenching zone in the prior art through multi-dimensional parameter matching, significantly improving the comprehensive mechanical properties and service life of threaded joints.
[0048] Preferably, the application scenarios of the threaded joint include low-wear scenarios and high-wear scenarios; if the application scenario is a low-wear scenario, the laser spot is determined to be a flat-topped circular spot; if the application scenario is a high-wear scenario, the laser spot is determined to be a rectangular spot.
[0049] This invention selects the spot type according to the wear characteristics of drilling conditions, which helps to optimize joint performance.
[0050] Understandably, the aforementioned low-wear scenarios are common in vertical wells, cluster wells, and similar operating conditions. Under these conditions, torque levels are relatively low, the threading frequency is normal, and the risk of fretting wear and sticking on the thread contact surface is small; wear is the conventional failure mode. The laser spot is determined to be a flat-topped circular spot because it is obtained through a laser beam shaping system, resulting in relatively uniform energy from its center to its edge. Under the action of this spot, the material surface is heated uniformly, the process window is wide, robustness is high, and a hardened layer of uniform depth and consistent structure is easily formed, enabling it to meet the conventional wear-resistant requirements of low-wear scenarios with extremely high process stability.
[0051] Conversely, the high-wear scenarios typically refer to complex conditions such as horizontal wells, extended reach wells, and ultra-deep wells. Under these conditions, the drill string must withstand extremely high and drastically fluctuating torque, with frequent threading and unthreading, resulting in significant thread wear, accompanied by intense fatigue and impact loads. In such cases, a rectangular laser spot is chosen. During scanning, the rectangular spot provides linear synchronous heating, with heat input perfectly synchronized in the vertical direction, ensuring a highly uniform hardened layer depth without weak points. This highly uniform hardened layer forms a symmetrical residual compressive stress field, effectively suppressing the initiation and propagation of fatigue cracks, and significantly improving resistance to severe wear, impact, and fatigue. If a flat-topped circular laser spot were used in such scenarios, its process window or stress field distribution characteristics might not be as well suited to the high-torque fluctuation conditions as the rectangular spot, leading to insufficient fatigue and severe wear resistance.
[0052] Furthermore, the distinction between low-wear and high-wear scenarios can be based on drilling depth, formation rock conditions, drill string design parameters, etc., which can be determined by those skilled in the art based on stress analysis results under actual working conditions. These parameters can usually be determined during the drilling engineering design phase, facilitating the pre-setting of process plans before processing. For example, when the well type is a vertical well or a cluster well, and the well inclination angle is small with stable torque fluctuations, it can usually be identified as a low-wear scenario; when the drilling depth exceeds 5000 meters, the well inclination angle exceeds 30 degrees (such as in horizontal wells or the build-up section of extended reach wells), or the design torque is extremely high and fluctuates violently, it can usually be identified as a high-wear scenario. It should be noted that the above values are only typical empirical thresholds and not absolute limits.
[0053] In summary, this invention avoids performance mismatches caused by fixed-parameter processes by adapting the laser spot type to specific scenarios. The flat-topped circular laser spot focuses on increasing hardness to resist wear, while the rectangular laser spot focuses on increasing toughness to resist impact. This differentiated design ensures the reliability of the joint in specific service environments and significantly extends the service life of the drill pipe joint.
[0054] To facilitate understanding of the technical solution of this invention, the basic structure of the threaded joint will first be described below with reference to the accompanying drawings. Figure 1 and Figure 2 As shown, the threaded joint includes an external thread 1 and an internal thread 4, which are connected by a threaded fit. Figure 1 The external thread 1 is marked with the external thread quenching area 2. Figure 2 The internal thread 4 is marked with the internal thread quenching area 5. This area 2 and 5 is the actual effective range of the high-precision laser quenching of this invention. Figure 3 As shown, the centerline of the threaded joint is the thread axis 3. The specific structure of the thread profile includes the thread bearing flank 6, the thread guiding flank 9, the thread crest 7, and the thread root arc 8. The thread bearing flank 6 and the thread guiding flank 9 are the main contact surfaces during thread mating and are also the target areas for laser quenching in this invention. The thread root arc 8 is a stress concentration area, and this invention requires avoiding laser energy coverage of this area during quenching. The thread taper line 10 reflects the taper characteristics of the threaded joint. Figure 4 , Figure 5 The laser quenching processes on the guide side and the load-bearing side of the external thread are shown respectively; Figure 7 , Figure 8 The laser quenching process is shown on the guide side and the load-bearing side of the internal thread, respectively. Figures 4 to 8 The specific position and angle relationship during laser quenching is further shown, wherein the quenching laser beam 12 emitted by the external thread laser 11 or the internal thread laser 13 acts on the thread bearing tooth side 6 or the thread guiding tooth side 9 at a specific irradiation angle. Figure 9 A schematic diagram of the thread profile parameters of the threaded connector is shown, which serves as the basis for subsequent formula calculations of the spot size and irradiation angle.
[0055] Preferably, determining the size of the laser spot specifically includes: Calculate the linear length of the bearing side of the thread tooth based on the thread profile parameters of the threaded joint; When the laser spot is determined to be a flat-top circular spot, the diameter of the flat-top circular spot is 85% to 115% of the linear length of the bearing side, and can be 85%, 90%, 95%, 100%, 105%, 110%, 115% and any value between them; Alternatively, when the laser spot is determined to be a rectangular spot, the width of the rectangular spot is 85% to 115% of the linear length on the bearing side, and can be 85%, 90%, 95%, 100%, 105%, 110%, 115% and any value between them.
[0056] This invention matches the spot size with the linear length of the thread tooth bearing surface to address the problems of insufficient strengthening or safety hazards caused by the prior art's reliance on experience and lack of calculation basis for spot size selection. The linear length of the thread tooth bearing surface is a fixed geometric parameter, and the selection of the spot size directly determines the coverage area of the quenching zone and the boundary of the energy distribution.
[0057] Understandably, this invention chooses the linear length of the thread bearing side as the matching benchmark for the laser spot size (the diameter of a flat-topped circular spot or the width of a rectangular spot), based on a comprehensive consideration of the thread profile geometry and laser energy boundary control. In API standard tapered thread structures, the bearing side is typically the narrow face of the thread profile, and its linear length is less than that of the guide side. This area is not only a critical contact surface bearing the main axial load and torque transmission during tightening, but also a high-incidence area for fretting wear and sticking failure in actual drilling conditions. Setting the laser spot size based on the linear length of the bearing side ensures that the laser energy accurately covers this narrowest and most critical stress area, while utilizing its geometrically narrow facet characteristics as an energy cutoff boundary to prevent the laser heat-affected zone from spreading to non-target areas.
[0058] Understandably, this invention controls the spot size to be 85%~115% of the linear length of the bearing side, aiming to balance coverage integrity and thread root safety. If the spot size is too small, i.e., less than 85% of the linear length of the bearing side, it cannot completely cover the contact working surface of the thread tooth side, and the unquenched area will wear first, reducing the overall quenching effect. More seriously, a significant hardness abrupt change will form at the interface between the unquenched area (soft matrix) and the quenched area (hardened layer). Under alternating contact stress, stress concentration is prone to occur at this interface, becoming a source of microcrack initiation and accelerating fatigue failure. In addition, a spot that is too small also means that the energy density is too high, which may lead to local overheating or even melting, affecting the uniformity of the microstructure.
[0059] If the laser spot size is too large, exceeding 115% of the linear length on the bearing side, laser energy can easily overflow into the thread root arc region, leading to the formation of a hard and brittle martensitic structure at the thread root. The thread root is the region with the highest stress concentration coefficient, and the local stress level can reach the material's yield strength after tightening. Once a hard and brittle phase exists at the thread root, its plastic deformation capacity is significantly reduced, making it highly susceptible to becoming a crack initiation under alternating loads, leading to joint fracture. Furthermore, an excessively large laser spot size can also result in an excessively wide heat-affected zone, causing excessive heat diffusion into the matrix, potentially leading to overall thread deformation and affecting mating accuracy. Therefore, this application limits the laser spot size to 85%~115% of the linear length on the bearing side, which can be 85%, 90%, 95%, 100%, 105%, 110%, 115%, or any value between them. This range ensures comprehensive strengthening of the thread flank working surface while effectively avoiding the stress concentration zone at the thread root, significantly reducing the safety hazard of joint fracture.
[0060] Furthermore, the high-precision process of this invention can effectively constrain the laser action boundary, ensuring that no hardened layer is formed in the thread root arc region. This structural feature blocks the extension of hard and brittle martensite to the high stress concentration area, eliminating the crack initiation path from a physical structure perspective. Combined with the aforementioned 85%~115% spot matching ratio, the laser energy cutoff line is always located inside the junction of the straight section of the tooth flank and the thread root arc, thereby achieving high-precision control of the thread root hardening width approaching 0 mm in engineering measurements.
[0061] Preferably, the laser spot size is selected as 100% of the linear length of the bearing side, which achieves the highest matching degree. At this ratio, the laser energy precisely covers the entire bearing side working surface, and the edge maintains a safe distance from the tooth crest / root arc, maximizing material utilization and ensuring a high degree of overlap between the quenching area and the stress area. For a flat-topped circular laser spot, a diameter of 100% of the linear length ensures that the energy cutoff edge falls exactly at the tooth flank boundary; for a rectangular laser spot, a width of 100% of the linear length ensures that the uniform energy distribution area completely covers the contact surface. Those skilled in the art will understand that, considering factors such as clamping errors, thread machining tolerances, and laser beam divergence angle in actual processing, a deviation range of ±15% is necessary. This provides a reasonable process window for industrial production, ensuring the stability and repeatability of the process.
[0062] In summary, this invention, by calculating the linear length based on the tooth profile parameters and matching the spot size accordingly, not only improves the wear resistance of the thread surface but also eliminates the risk of tooth root cracking caused by improper spot size, ensuring the structural integrity and service reliability of the drill pipe joint under complex downhole conditions.
[0063] Preferably, determining the illumination angle of the laser beam includes: The angle between the central axis of the laser beam and the axis of the threaded joint is determined to be 30°~70°, which can be 30°, 40°, 50°, 60°, 70° and any value in between. The illumination angle includes the guide side illumination angle and the load-bearing side illumination angle, which are determined independently.
[0064] This invention controls the angle between the laser beam and the axis of the threaded joint to be 30°~70° to solve the problems of adjacent tooth obstruction and energy absorption efficiency caused by the thread taper, thereby achieving high-precision area control. Drill pipe joint threads have a taper (typically 1:4~1:16) and variable tooth flank angles (commonly 30°~45°). This geometry requires the laser beam to avoid interference from adjacent thread teeth during irradiation while ensuring effective energy coupling.
[0065] Understandably, if the angle between the laser beam and the axis is less than 30°, the incident angle is too small, and the laser beam may be blocked by adjacent thread teeth, failing to effectively irradiate the root of the bearing side or guide side, forming a quenching blind zone. Specifically, due to the existence of thread taper, the bearing side teeth block each other. When the angle is too small, the spatial trajectory of the laser spot cannot completely cover the root of the tooth flank, resulting in insufficient or no hardened layer thickness at the root of the tooth flank. When the thread is under stress, the root is often a stress concentration area. If the hardness of this area is insufficient, it is prone to plastic deformation or wear first, reducing the overall quenching effect. In addition, an excessively small angle may also cause the projected area of the laser spot on the tooth flank to be too large, diluting the energy density and failing to reach the austenitizing critical temperature.
[0066] If the angle is greater than 70°, the incident angle is too large, approaching parallel to the tooth lateral surface, reducing energy absorption efficiency and causing most of the energy to be reflected. According to the Fresnel reflection principle, the larger the laser incident angle, the higher the reflectivity of the material surface, and the less energy is actually absorbed for heating, resulting in low quenching efficiency. Furthermore, an excessively large angle may cause the laser spot to be elongated on the tooth lateral surface, leading to uneven energy density distribution and affecting quenching uniformity, resulting in inconsistent hardened layer thickness along the tooth lateral height direction. In addition, an excessively large angle may make the laser beam more likely to irradiate the crest or floor of the tooth, increasing the risk of accidental hardening, especially at the floor, which significantly increases the risk of cracking. Therefore, a range of 30° to 70° helps ensure that the laser energy effectively acts on the tooth lateral surface while avoiding the crest and floor.
[0067] Furthermore, the guide side and the load-bearing side have different geometric angles and different force requirements. Therefore, determining the irradiation angle independently allows for more precise control. Due to the presence of thread taper, the tilt angles of the guide side and the load-bearing side relative to the axis are not perfectly symmetrical, resulting in differences in their optimal clearance angle and vertical irradiation angle. If a uniform irradiation angle is used, it may result in one side having a suitable angle while the other side deviates, affecting the quenching quality. This invention allows the irradiation angles of the guide side and the load-bearing side to be determined independently, for example, calculated separately using the aforementioned formula, ensuring that the laser beam can act vertically or approximately vertically on their respective tooth flank surfaces. This independent control strategy avoids quenching blind spots caused by geometric obstruction, ensures a uniform distribution of the hardened layer thickness along the tooth flank height direction, and improves the laser energy absorption rate, reducing energy waste and demonstrating the advantages of high-precision process control of this invention.
[0068] In summary, by limiting the irradiation angle range and independently determining the angles of the guide side and the bearing side, this invention effectively solves the problems of laser reachability and energy coupling efficiency under complex thread profiles. This angle control strategy not only ensures precise coverage of the quenching zone but also eliminates the risk of uneven hardening layer or accidental hardening at the thread bottom caused by improper angles, ensuring the structural integrity and service reliability of the drill pipe joint under complex downhole conditions.
[0069] Preferably, both the irradiation angle on the bearing side and the irradiation angle on the guide side are the angles between the laser beam and the axis of the threaded joint; The formula for calculating the irradiation angle on the bearing side is:
[0070] in, For the irradiation angle on the bearing side, The linear length of the thread tooth on the bearing side. The radius of the tooth root arc, It is a tooth-shaped half-angle; The formula for calculating the guide side illumination angle is:
[0071] in, For the guide side illumination angle, The linear length of the thread guide side. The radius of the tooth root arc, It is a tooth-shaped half-angle.
[0072] This invention uses theoretical formulas to accurately calculate the irradiation angle, which helps achieve high-precision quenching and ensures the matching of process parameters with thread geometry. The above formula is derived based on the spatial geometric relationship of the thread profile, and its physical meaning is to calculate the optimal angle for the laser beam to be perpendicular or approximately perpendicular to the tooth flank surface without obstructing adjacent teeth. See details... Figure 6 The enlarged schematic diagram shows the spatial relationship between the quenching laser beam 12 and the thread bearing tooth side 6 and the thread guiding tooth side 9, as well as the irradiation angle. and Definition.
[0073] The formula incorporates the radius of the tooth root arc. and tooth-shaped half-angle The design fully considers the effects of root clearance and flank normal direction. The calculated angle ensures that the laser beam acts perpendicularly or nearly perpendicularly on the thread flank surface, avoiding quenching blind zones caused by geometric obstruction, ensuring uniform distribution of hardened layer thickness along the flank height, and improving laser energy absorption rate.
[0074] Understandably, the numerator in the calculation formula represents the projected component of the thread flank in the direction perpendicular to the axis, while the denominator represents the equivalent geometric path after considering the root radius transition. The angle calculated using the arctangent function is essentially the geometric compensation angle required for the laser beam to avoid interference between adjacent thread teeth while maximizing perpendicular incidence on the current thread flank surface. Because drill pipe joint threads have a taper (typically 1:4 to 1:16) and variable flank angles (commonly 30° to 45°), there is mutual obstruction between the bearing-side teeth. If a fixed angle is used instead of the formula, it may be difficult to adapt to the geometric differences of different thread profiles (such as APIV-038R, V-050, etc.), leading to fluctuations in quenching quality.
[0075] In summary, by defining the irradiation angle calculation formula and independently determining the angles of the guide side and the bearing side, this invention effectively solves the problems of laser reachability and energy coupling efficiency under complex thread profiles. This angle control strategy not only ensures precise coverage of the quenching zone but also eliminates the risk of uneven hardening layer or accidental hardening at the thread bottom caused by improper angles, ensuring the structural integrity and service reliability of the drill pipe joint under complex downhole conditions.
[0076] like Figure 9 As shown, the geometric parameters of the thread profile, including the thread height. , radius of tooth base arc , tooth shape half angle and taper These parameters, together, determine the linear length of the thread's bearing side and guiding side. These parameters are the basis for the precise matching of the spot size and irradiation angle in this invention. Among them, the thread height... This refers to the radial height from the crest to the root of the thread in the direction perpendicular to the axis, which determines the total height reference available for laser hardening of the thread flank; the radius of the root arc. This refers to the radius of curvature of the transition arc at the root of the thread. This area is the stress concentration zone during thread mating and defines the radius of the root arc. The boundary can effectively define the laser energy cutoff line, preventing the hardened layer from extending to the tooth floor and forming hard and brittle martensite; tooth profile half-angle Taper refers to the angle between the thread flank profile and the plane perpendicular to the axis. It directly affects the incident projection area and normal perpendicularity of the laser beam on the thread flank, and is an important geometric variable for calculating the irradiation angle. This reflects the rate of change of the thread diameter along the axial direction. Its physical meaning is the change in diameter (usually expressed as a ratio, such as 1:4 to 1:16) for every unit increase in axial length. The presence of taper causes an asymmetrical distribution of the geometric projections of the bearing side and the guiding side, potentially leading to spatial interference between adjacent thread flanks. These four parameters are coupled together, constraining the effective area of the laser action through spatial geometric projection and the principle of space-avoidance interference. This provides a geometric basis for the subsequent quantitative matching of the laser spot size and the independent calculation of the irradiation angle.
[0077] Preferably, the formula for calculating the linear length of the thread tooth bearing side is:
[0078] in, The linear length of the thread tooth on the bearing side. The height of the tooth profile. The radius of the tooth root arc, The taper of the threaded connector. It is a tooth-shaped half-angle.
[0079] This invention provides the linear length of the thread tooth bearing side. The specific calculation formula provides a precise quantitative basis for selecting the laser spot size, ensuring the match between the laser energy coverage area and the geometric features of the thread flank. This formula comprehensively considers the tooth height. , radius of tooth base arc Taper and tooth-shaped half angle The influence of these parameters means that each parameter has a clear physical meaning in the laser quenching process. Tooth height The total usable height of the thread flank is determined and serves as the fundamental reference for calculating the linear length; the root radius... The range of the stress concentration region is determined, and the formula is subtracted. The design aims to subtract the root arc transition zone from the total tooth height to ensure that the calculated linear length only includes the straight portion suitable for quenching, avoiding laser energy coverage of the root arc area; tooth profile half-angle The degree of tilt on the tooth side determines the incident projection area of the laser beam; taper It determines the rate of change of the thread diameter along the axial direction, affecting the geometric symmetry between the load-bearing side and the guide side.
[0080] Understandably, taper The existence of this factor means that the linear lengths of the load-bearing side and the guide side are not perfectly symmetrical. This formula is modified by subtracting... The term corrects for the geometric deviation caused by the taper. Specifically, since drill pipe joint threads are typically tapered threads (taper range 1:4~1:16), the inclination angle of the thread flank relative to the axis is not exactly the same on the load-bearing side and the guide side. The load-bearing side mainly bears the shear stress generated by axial tensile force, and its geometric projection length is significantly affected by the taper. The denominator in the formula... This reflects the geometric projection relationship under the combined effect of taper and tooth angle, while the molecules... The term is a taper correction term specific to the bearing side. If the taper effect is ignored and the calculation is performed directly according to the standard straight thread profile, the calculated linear length will deviate from the actual geometric length.
[0081] The present invention calculates using this formula Combining this with the aforementioned 85%~115% ratio ensures precise coverage of the bearing-side working surface by the light spot. For example, for an APINC50 connector (APIV-038R thread profile), substituting typical parameters ( , , , ), calculated Approximately 2.8mm. Based on this value, a flat-topped circular spot with a diameter of 3mm (approximately...) was selected. (107%), ensuring that the edge of the light spot falls precisely inside the junction of the straight section of the tooth flank and the arc of the tooth root, thus achieving comprehensive strengthening of the working surface while effectively avoiding the stress concentration zone at the tooth root. This parameter determination method based on precise geometric calculations eliminates reliance on operator experience, significantly improves the stability and repeatability of the process, and ensures the consistency of quenching quality for joints of different batches and specifications.
[0082] In summary, this invention, by introducing a linear length calculation formula that includes a taper correction term, not only improves the wear resistance of the thread surface but also eliminates the risk of accidental hardening of the thread root due to improper spot size, ensuring the structural integrity and service reliability of the drill pipe joint under complex downhole conditions. Those skilled in the art will understand that this formula is applicable to various API standard threads and non-standard threads; accurate linear lengths can be obtained simply by substituting the corresponding thread profile parameters, demonstrating its wide applicability.
[0083] Preferably, the formula for calculating the linear length of the thread guide side is:
[0084] in, The linear length of the thread guide side. The height of the tooth profile. The radius of the tooth root arc, The taper of the threaded connector. It is a tooth-shaped half-angle.
[0085] Similarly, this invention provides the linear length of the thread guide side. The calculation formula provides an independent quantitative basis for the precise determination of the guide-side spot size and irradiation angle. This formula comprehensively considers tooth height. , radius of tooth base arc Taper and tooth-shaped half angle The influence of these parameters means that each parameter has a clear physical meaning in the laser quenching process. Tooth height The total usable height of the thread flank is determined and serves as the fundamental reference for calculating the linear length; the root radius... The range of the stress concentration region is determined, and the formula is subtracted. The design aims to subtract the root arc transition zone from the total tooth height to ensure that the calculated linear length only includes the straight portion suitable for quenching, avoiding laser energy coverage of the root arc area; tooth profile half-angle The degree of tilt on the tooth side determines the incident projection area of the laser beam; taper It determines the rate of change of the thread diameter along the axial direction, affecting the geometric symmetry between the load-bearing side and the guide side.
[0086] Understandably, compared to the formula for the load-bearing side, the formula for the guiding side adds... Term, and the denominator is This reflects the geometric asymmetry between the guide side and the bearing side. Specifically, since drill pipe joint threads are typically tapered threads (taper range 1:4~1:16), the inclination angle of the thread flanks relative to the axis is not exactly the same on the bearing side and the guide side. The bearing side mainly bears the shear stress generated by axial tensile force, while the guide side mainly bears the guiding force and radial force during the threading process. Taper The presence of this distortion causes the projection of the thread profile along the axial direction to be distorted. The projection angles of the bearing side and the guide side relative to the plane perpendicular to the axis are opposite. Therefore, in the formula derivation, the signs of the taper correction terms are opposite (subtraction for the bearing side and addition for the guide side), and the trigonometric function combinations in the denominator are also different. If this geometric asymmetry is ignored and the formula for the bearing side is directly applied to calculate the length of the guide side, it will lead to significant deviations in the calculation results.
[0087] Calculate separately and This method helps to determine the optimal spot size and irradiation angle for the load-bearing side and the guide side respectively, enabling independent optimization control on both sides. This parameter determination method based on precise geometric calculations eliminates the reliance on operator experience, significantly improves the stability and repeatability of the process, and ensures the consistency of quenching quality for joints of different batches and specifications.
[0088] In summary, this invention, by introducing a linear length calculation formula that includes a taper correction term, not only improves the wear resistance of the thread surface but also eliminates the risk of accidental hardening of the thread root due to improper spot size, ensuring the structural integrity and service reliability of the drill pipe joint under complex downhole conditions. Those skilled in the art will understand that this formula is applicable to various API standard threads and non-standard threads; accurate linear lengths can be obtained simply by substituting the corresponding thread profile parameters, demonstrating its wide applicability.
[0089] Preferably, the illumination angle on the guide side and the illumination angle on the load side are also independently compensated, with the angle compensation range being 0° to 10°, which can be 0°, 2°, 5°, 8°, 10° and any value between them.
[0090] This invention allows for 0°~10° angle compensation based on the calculated values, in order to address systematic errors in actual processing and further optimize energy distribution, ensuring the stable reproduction of theoretical processes in actual production. The theoretical formula calculates ideal geometric angles, which are optimal solutions derived from standard thread profile parameters. However, in actual industrial production environments, various uncontrollable factors may cause deviations between the theoretical and actual optimal angles. Specifically, the sources of error mainly include: coaxiality errors in workpiece clamping, thread profile angle tolerances in thread processing itself, positioning accuracy errors in the laser head motion system, and minute thermal deformations caused by workpiece heating during laser quenching. If the angle calculated strictly according to the theoretical formula is followed, the cumulative errors mentioned above may cause the laser spot to shift on the actual thread flank, affecting quenching accuracy.
[0091] Understandably, the angle compensation range is limited to 0°~10°, which aims to balance adjustment flexibility and energy coupling efficiency. A compensation angle of 0° means directly using the theoretically calculated angle, suitable for ideal working conditions with extremely high machining accuracy and perfect clamping. A positive compensation angle (0°~10°) means appropriately increasing the angle between the laser beam and the axis based on the theoretical angle. If the compensation angle is too large, i.e., exceeding 10°, the incident angle is too large, approaching parallel to the tooth flank surface, and the energy absorption efficiency is significantly reduced. According to the Fresnel reflection principle, the larger the laser incident angle, the higher the reflectivity of the material surface, and the less energy is actually absorbed for heating, resulting in low quenching efficiency and possibly failing to reach the austenitizing temperature. Furthermore, an excessively large angle may cause the laser spot to elongate and deform on the tooth flank surface, resulting in uneven energy density distribution, affecting quenching uniformity, and causing inconsistent distribution of the hardened layer thickness along the tooth flank height direction. In addition, an excessively large compensation angle may also make the laser beam more likely to irradiate the crest or floor arc area of the tooth, increasing the risk of accidental hardening, especially accidental hardening of the floor, which significantly increases the risk of cracking.
[0092] If the compensation angle is too small, i.e., less than 0° (negative compensation), it means reducing the angle between the laser beam and the axis. While this theoretically improves perpendicularity, in practice, due to the thread taper, the bearing-side teeth block each other. If the angle is reduced too much, the laser beam may be blocked by adjacent thread teeth, failing to effectively irradiate the root of the bearing or guide side, creating a quenching blind zone. Specifically, when the angle is less than the theoretical value, the spatial trajectory of the laser spot cannot completely cover the root of the tooth flank, resulting in insufficient or no hardened layer thickness at the root. When the thread is under stress, the root is often a stress concentration area. If the hardness of this area is insufficient, it is prone to plastic deformation or wear first, reducing the overall quenching effect. Therefore, limiting the compensation range to no less than 0° is to ensure that the risk of blocking by adjacent teeth is avoided and that the laser energy is effectively applied to the tooth flank surface.
[0093] Furthermore, independent angle compensation on the guide side and the load-bearing side enables more precise control. Due to the presence of thread taper, the tilt angles of the guide side and the load-bearing side relative to the axis are not perfectly symmetrical, resulting in differences in their optimal clearance angle and vertical irradiation angle. In actual machining, the sources of error on both sides may also differ. For example, the load-bearing side experiences greater force and requires higher uniformity of quenching depth, potentially requiring a larger compensation margin to compensate for thermal deformation; while the guide side prioritizes fit precision and may require stricter angle control. This invention allows for independent compensation on both sides, for example, 5° compensation on the load-bearing side and 3° compensation on the guide side, ensuring that the laser beam can act vertically or nearly vertically on their respective tooth flank surfaces. This independent control strategy avoids quenching blind spots caused by geometric obstruction, ensures uniform distribution of the hardened layer thickness along the tooth flank height direction, and simultaneously improves the laser energy absorption rate, reducing energy waste and demonstrating the advantages of high-precision process control in this invention.
[0094] In summary, by limiting the angle compensation range and independently determining the compensation values for the guide side and the bearing side, this invention effectively solves the problem of deviation between theoretical calculations and actual processing. This angle control strategy not only ensures precise coverage of the quenching zone but also eliminates the risk of uneven hardening layer or accidental hardening at the tooth bottom caused by improper angles, ensuring the structural integrity and service reliability of the drill pipe joint under complex downhole conditions.
[0095] Preferably, the laser power and scanning speed for laser quenching are determined based on the properties of the joint material, including: When the connector material is medium carbon alloy steel, the laser power is 300W~2000W, which can be 300W, 500W, 800W, 1000W, 1500W, 2000W and any value between them, and the scanning speed is 10mm / s~60mm / s, which can be 10mm / s, 20mm / s, 30mm / s, 40mm / s, 50mm / s, 60mm / s and any value between them; When the connector material is aluminum alloy, the laser power is 300W~1000W, which can be 300W, 500W, 800W, 1000W and any value between them, and the scanning speed is 2mm / s~10mm / s, which can be 2mm / s, 4mm / s, 6mm / s, 8mm / s, 10mm / s and any value between them.
[0096] This invention controls the specific numerical range of laser power and scanning speed, which helps to ensure that the energy density of the process falls within the critical energy density range of the material. The thickness of the hardened layer is positively correlated with the laser energy density and negatively correlated with the scanning speed. By precisely matching the combination of power and speed, an ideal hardened layer thickness can be obtained while avoiding the melting of the substrate. The selection of power and speed is essentially based on the thermophysical properties of the material (such as thermal conductivity, specific heat capacity, austenitizing temperature, etc.) to determine the appropriate energy density input, ensuring that the material surface reaches the AC3 temperature without melting or burning.
[0097] Understandably, medium carbon alloy steels (such as 4145H and 4137H) are commonly used materials for drill pipe joints, possessing good hardenability and comprehensive mechanical properties. If the laser power is less than 300W or the scanning speed is greater than 60mm / s, the energy input is insufficient, the material surface cannot reach the austenitizing temperature, or the cooling rate is insufficient, resulting in a shallow hardened layer or even failure to form martensite, thus failing to achieve surface strengthening. If the laser power is greater than 2000W or the scanning speed is less than 10mm / s, the energy input is excessive, which may cause the material surface to melt, burn, or produce quenching cracks. Furthermore, excessive heat input can lead to an excessively wide heat-affected zone, affecting thread accuracy and increasing the risk of accidental hardening at the thread root. By controlling the power of medium carbon alloy steel between 300W and 2000W and the speed between 10mm / s and 60mm / s, it is more helpful to ensure sufficient hardened layer thickness and avoid defects caused by extreme process parameters.
[0098] Understandably, aluminum alloys exhibit significantly different thermophysical properties compared to steel. The thermal conductivity of aluminum alloys (approximately 237 W / (m·K)) is much higher than that of steel (approximately 50 W / (m·K) for low-carbon steel). During laser heating, the heat from aluminum is rapidly conducted to the substrate, making it difficult to maintain a stable surface temperature. Therefore, aluminum alloy joints should utilize a more concentrated laser spot with a power range limited to 300W~1000W to avoid overheating. If the laser power exceeds 1000W or the scanning speed is less than 2mm / s, due to aluminum's high thermal conductivity, although heat dissipates quickly, excessively high power may still cause localized areas with lower melting points (such as eutectic phases) to melt, resulting in porosity or cracks. If the power is less than 300W or the scanning speed is greater than 10mm / s, heat dissipation is too rapid, and the surface temperature cannot reach the threshold required for strengthening, preventing the formation of an effective hardened layer. By controlling the power of the aluminum alloy between 300W and 1000W and the speed between 10mm / s and 60mm / s, it is easier to compensate for heat conduction loss while avoiding overheating defects.
[0099] Furthermore, medium-carbon alloy steels with different carbon contents exhibit varying power sensitivity. 4145H steel, with its higher carbon content than 4137H steel, has better hardenability. 4137H is power-sensitive, requiring slightly higher power or slightly lower speed to ensure martensitic transformation. For the same hardened layer thickness, 4137H requires higher power and a lower speed than 4145H. The power and speed windows provided by this invention encompass these material differences, making the process widely applicable.
[0100] In summary, this process parameter design enables engineering matching of the hardened layer thickness of joints made of different materials. Medium carbon alloy steel achieves a thick hardened layer through a high-power window, while aluminum alloys avoid overheating through a low-power window, which further helps to stably obtain threaded joints with ideal hardened layer thickness. This parameter determination method based on the thermophysical properties of materials avoids quenching failures caused by empirically set parameters in existing technologies, ensuring that the energy density always falls within the effective quenching range, allowing the resulting products to be optimally matched to the specific downhole service environment.
[0101] Preferably, the laser power and scanning speed satisfy the following energy density relationship:
[0102] in, The critical energy density of the joint material is 15 J / mm². 2 ~60J / mm 2 ; Laser power; For scanning speed; It represents the diameter of a flat-topped circular light spot or the width of a rectangular light spot.
[0103] This invention introduces a critical energy density formula, establishing a quantitative link between material properties and process parameters, thus ensuring the scientific rigor and repeatability of process design. Critical energy density Critical energy density refers to the energy density range within which the surface layer of a material reaches the AC3 temperature (austenitization initiation temperature) without melting or burning. Different materials have different critical energy density ranges. This invention controls the critical energy density. The value range is 15J / mm 2 ~60J / mm 2 This range is estimated based on the heat conduction equation and parameters such as density, specific heat capacity, thermal conductivity, austenitizing temperature, and melting point of commonly used steels for drill pipe joints. In process design, the material properties are first determined... Value, then select the light spot and speed Finally, the required power is calculated in reverse. This method of determining process parameters based on material properties avoids quenching failures caused by trial and error based on experience, and ensures that the energy density always falls within the effective quenching range.
[0104] Understandably, the lower limit of the critical energy density range is 15 J / mm². 2 This is the minimum energy threshold to ensure effective quenching. If the critical energy density... Less than 15J / mm 2 This means that the energy input per unit area to the material surface is insufficient, and the surface temperature cannot reach the austenitization initiation temperature (AC3), or although it reaches AC3, the holding time is insufficient, resulting in incomplete austenitization. During the subsequent self-excited cooling process, sufficient martensitic transformation cannot occur, leading to a shallow hardened layer or even failure to form a martensitic structure, thus failing to achieve surface strengthening. For materials with high thermal conductivity (such as aluminum alloys), heat will be rapidly conducted to the matrix. If the energy density is below this lower limit, the surface temperature is difficult to maintain, and the risk of quenching failure is higher. Therefore, the critical energy density E should be controlled to be no less than 15 J / mm². 2 This is to ensure that the surface of the material can receive enough energy input to complete the phase transition.
[0105] Understandably, the upper limit of the critical energy density range is 60 J / mm². 2 It is the highest energy threshold to avoid material damage. If the energy density... Greater than 60J / mm 2This means that excessive energy input may cause the material surface temperature to exceed its melting point, leading to surface melting, burning, or the formation of vaporization pits, thus compromising the integrity of the thread surface. Furthermore, excessively high energy density can result in excessive heat input, an excessively wide heat-affected zone, and excessive heat diffusion towards the thread root, potentially causing unintended hardening of the thread root. The thread root is the area with the highest stress concentration; if a hard and brittle martensitic structure is present, it is highly susceptible to becoming a crack initiation under alternating loads, leading to joint fracture. Simultaneously, excessive heat input can also increase workpiece thermal deformation, affecting the thread fit accuracy. Therefore, controlling... Not greater than 60J / mm 2 This is to avoid the risks of melting, cracking, and accidental hardening of the tooth root while ensuring the hardening effect.
[0106] It should be noted that although the hardened layer thickness parameter is not directly stated in the formula, the critical energy density in the formula is... The value of is strongly related to the required hardened layer thickness. According to the heat conduction principle of laser quenching, within the allowable range of the material's critical energy density, the hardened layer thickness and energy density are approximately positively correlated. Specifically, when a thicker hardened layer is required (such as in high-wear areas), it means that more heat input is needed to extend the austenitized region deeper into the matrix; therefore, a higher energy density needs to be selected. The value is then used to calculate a higher power using a formula. or lower speed When a thinner hardened layer is required (such as in non-high wear areas), a lower energy density needs to be selected to avoid overheating or affecting the properties of the matrix. The value is then used to calculate the lower power. or higher speed This is achieved through energy density. The method of using the thickness as an intermediate variable to correlate with the process parameters not only ensures that the process parameters conform to the physical properties of the material (within the critical range), but also achieves the control of the thickness of the hardened layer.
[0107] Preferably, through the coordinated control of the energy density and process window, the thickness of the hardened layer is stabilized within the range of 0.1 mm to 0.5 mm. When the thickness is less than 0.1 mm, the reinforced layer is too shallow and is easily worn through under alternating contact stress; when the thickness is greater than 0.5 mm, the heat-affected zone extends excessively into the substrate, easily causing thread dimensional deviations or deterioration of subsurface toughness. This invention, by inversely controlling power and speed through the critical energy density relationship, helps to ensure that the depth of the hardened layer falls within this preferred range, achieving a balance between surface strengthening and substrate properties.
[0108] It should be noted that the critical energy density range varies for different materials. For medium-carbon alloy steel (such as 4145H), its thermal conductivity is relatively low, and heat dissipation is slow, so its critical energy density range can be as low as 15 J / mm². 2 ~60J / mm 2 For aluminum alloys, whose thermal conductivity is higher than that of steel, heat is rapidly conducted to the substrate during laser heating. To compensate for this heat loss and ensure the surface reaches the phase transition temperature, a higher energy density input is required. Therefore, its critical energy density range can be 20 J / mm². 2 ~60J / mm 2 .
[0109] It should be noted that the upper limit of laser power set for aluminum alloy (1000W) is lower than that for medium carbon alloy steel (2000W), but its lower limit of critical energy density (20J / mm²) is lower. 2 However, it is higher than that of medium carbon alloy steel (15J / mm). 2 This is because aluminum alloys have extremely high thermal conductivity, and excessively high laser power density can cause instantaneous overheating of the surface, resulting in process defects such as melting and vaporization. Therefore, its power upper limit is subject to stricter damage prevention restrictions. Under this constraint, in order to meet the higher lower limit requirement of critical energy density for aluminum alloys, a lower scanning speed should be matched to increase the laser's interaction time on the material surface, thereby ensuring that sufficient energy is input to achieve adequate quenching without causing surface damage.
[0110] In summary, by controlling the energy density relationship and the critical energy density range, this invention effectively solves the problem of blind determination of process parameters. This quantitative calculation method based on material properties ensures that joints of different materials and thickness requirements can obtain an ideal hardened layer, avoiding quenching failure or workpiece damage caused by improper energy input. This demonstrates the advantages of high-precision process control of this invention and ensures the structural integrity and service reliability of drill pipe joints under complex downhole conditions.
[0111] Preferably, a laser beam is used to scan and quench the guide side and the load-bearing side of the threaded joint, specifically including: First, laser hardening scanning is performed on the guide side of the threaded joint; After completing the quenching scan on the guide side, the bearing side of the threaded joint is then subjected to laser quenching scan. In the laser quenching process, the scanning direction is always from the large end to the small end of the threaded joint, where the laser beam moves to scan.
[0112] The specific method of controlling the scanning sequence and direction in this invention helps to optimize the distribution of residual stress and ensure the performance stability of threaded joints under complex service conditions. The guiding side and the load-bearing side of a threaded joint perform different functions during service; the guiding side focuses on wear resistance, friction reduction, and fit accuracy, while the load-bearing side focuses on wear resistance, impact resistance, and connection strength. Therefore, by performing step-by-step scanning and utilizing the laser heat conduction effect, independent optimization and coordinated matching of the performance on both sides can be achieved.
[0113] Understandably, during the quenching of the bearing side, the high-temperature heat generated by the laser is conducted to the already quenched guide side through the matrix, causing the surface temperature of the guide side to rise back to the tempering temperature range, which is equivalent to performing a self-tempering treatment on the guide side. This process sequence effectively improves the toughness of the guide side, eliminates some quenching stress, reduces the brittleness of the guide side, and avoids cracking or peeling due to excessive hardness of the guide side during subsequent threading and unthreading. If the sequence is reversed, with the bearing side processed first and the guide side processed later, the bearing side may be tempered by the heat from the guide side scanning. The bearing side is a critical part of the thread that bears the load and needs to maintain high hardness and strength to resist impact loads. If the bearing side undergoes self-tempering softening, its hardness may decrease, leading to a decline in impact resistance. When subjected to large tensile or torque forces during drilling, it is prone to plastic deformation or even fracture, posing a safety hazard.
[0114] Preferably, the high-precision laser hardening treatment described above helps stabilize the hardness of the hardened layer on the thread bearing side and guide side surfaces within the range of 45HRC to 60HRC. The lower limit of 45HRC ensures that the contact working surface has the basic hardness to resist fretting wear, avoiding premature failure of the soft matrix; the upper limit of 60HRC avoids peeling or microcrack propagation caused by excessively brittle surface layers. Combined with the scanning sequence of first the guide side and then the bearing side, the hardness of the bearing side is usually slightly higher than that of the guide side (the difference is about 1 to 3HRC). This hardness gradient not only ensures the wear resistance and impact resistance of the bearing side, but also improves the toughness of the guide side through the self-tempering effect, meeting the mechanical matching requirements under complex drilling conditions.
[0115] Understandably, this invention limits the scanning direction of laser quenching to from the large end to the small end of the threaded joint in order to ensure the consistency of the quenching process and the controllability of heat accumulation. Drill pipe joint threads are typically tapered threads, with the large end having a large diameter, large mass, and large heat capacity, while the small end has a small diameter, small mass, and small heat capacity. Scanning from the large end to the small end moves the laser heat source from the area with high heat capacity to the area with low heat capacity, which is beneficial for uniform heat diffusion and avoids excessive heat accumulation in a certain area. If the scanning direction is reversed, scanning from the small end to the large end, heat will gradually accumulate towards the large end, which is precisely the area with the greatest stress and the highest performance requirements (such as the aforementioned high-wear area). Excessive heat accumulation may lead to excessively high temperatures in the large end area, causing grain coarsening or increased thermal deformation, affecting the thread fit accuracy. Furthermore, scanning from the large end to the small end also conforms to conventional practices in thread processing and inspection, facilitating the control system to synchronously adjust power and speed, ensuring process stability along the axial direction.
[0116] In summary, by controlling the scanning sequence of the guide side first and then the bearing side, as well as the scanning direction from the large end to the small end, this invention effectively solves the problems of thermal interference and microstructure matching during multi-faceted quenching. This process path design not only ensures the toughness of the guide side and the strength of the bearing side, but also controls the risk of heat accumulation and deformation, providing a stable process environment for the precise implementation of parameters such as the aforementioned spot size, irradiation angle, and energy density, thus ensuring the structural integrity and service reliability of the drill pipe joint under complex downhole conditions.
[0117] Secondly, the present invention provides a threaded connector that has been treated with the laser hardening method described in the first aspect. The threaded connector provided by the present invention, due to the use of the aforementioned high-precision laser hardening method, exhibits a uniform and stable hardened layer on the thread flank surface, high matching degree between the laser spot and the tooth profile, no unexpected hardening at the tooth root, and good microstructure matching with the working conditions. This connector demonstrates excellent wear resistance and toughness under heavy load or impact conditions, significantly extending its service life.
[0118] The embodiments of the present invention are described in detail below. These embodiments are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0119] Example 1 This embodiment provides a high-precision laser quenching method for threaded joints, applied to APINC50 joints, with the material being quenched and tempered 4145H medium carbon alloy steel.
[0120] Step 1: Determine the shape of the laser spot.
[0121] Based on the application scenario of horizontal wells / extended reach wells / ultra-deep wells (high wear scenarios), the laser spot is determined to be a rectangular spot.
[0122] Step 2: Determine the size of the laser spot.
[0123] According to APIV-038R thread profile parameters ( , , , ), calculate the linear length on the bearing side .
[0124] Finally, a rectangular light spot with a width of 3mm (approximately) was selected. 107% of the total.
[0125] Step 3: Calculate the illumination angle.
[0126] Calculate the linear length of the thread guide side. .
[0127] Calculate the irradiation angle on the bearing side according to the formula. , Guide side illumination angle .
[0128] The guide-side illumination angle and the load-bearing side illumination angle are also independently compensated to finally determine the load-bearing side laser illumination angle. Take 43 degrees as the guide side laser irradiation angle. Take 46 degrees.
[0129] Step 4: Determine the power and speed.
[0130] Critical energy density of joint materials 15J / mm 2 Scanning speed Width of the rectangular light spot .
[0131] According to the energy density relationship The laser power was calculated. .
[0132] Step 5: Scanning and quenching.
[0133] First, scan the guide side from the large end to the small end. After completion, return to the large end and then scan the bearing side from the large end to the small end.
[0134] Example 2 The difference between this embodiment and Embodiment 1 is that the application scenario is a vertical well or a cluster well (low wear scenario), and the laser spot is determined to be a flat-topped circular spot with a diameter of 3mm.
[0135] The remaining steps are the same as in Example 1.
[0136] Example 3 The difference between this embodiment and Embodiment 1 is that the connector material is aluminum alloy. The critical energy density of the connector material... 20J / mm 2 Scanning speed Width of the rectangular light spot The calculated laser power .
[0137] The remaining steps are the same as in Example 1.
[0138] Example 4 The difference between this embodiment and Embodiment 1 is that: the guide-side illumination angle and the bearing-side illumination angle are not compensated for, and the final laser illumination angle on the bearing side is determined. Take 38 degrees as the guide side laser irradiation angle. Take 41 degrees.
[0139] The remaining steps are the same as in Example 1.
[0140] Example 5 The difference between this embodiment and embodiment 1 is that in step 5, the carrier side is scanned from the large end to the small end first, and after completion, the scan returns to the large end, and then the guide side is scanned from the large end to the small end.
[0141] The remaining steps are the same as in Example 1.
[0142] Example 6 This embodiment provides a high-precision laser quenching method for threaded joints, applied to API 5 1 / 2FH external threaded joints, using quenched and tempered 4145H medium carbon alloy steel. This embodiment focuses on parameter matching for the APIV-050R thread profile.
[0143] Step 1: Determine the shape of the laser spot.
[0144] Based on the application scenario of high wear and tear, the laser spot is determined to be a rectangular spot.
[0145] Step 2: Determine the size of the laser spot.
[0146] Based on the APIV-050R thread profile parameters, the thread height is known. radius of tooth base arc Taper of threaded joint , tooth shape half angle .
[0147] Calculate the linear length of the thread tooth bearing side .
[0148] Finally, a rectangular light spot with a width of 4mm (approximately) was selected. (108%).
[0149] Step 3: Calculate the illumination angle.
[0150] Calculate the linear length of the thread guide side. .
[0151] Calculate the irradiation angle on the bearing side according to the formula. , Guide side illumination angle .
[0152] The guide-side illumination angle and the load-bearing side illumination angle are also independently compensated to finally determine the load-bearing side laser illumination angle. Take 52 degrees as the guide side laser irradiation angle. Take 54 degrees.
[0153] Step 4: Determine the power and speed.
[0154] Critical energy density 15J / mm 2 Scanning speed Width of the rectangular light spot .
[0155] According to the energy density relationship The laser power was calculated. .
[0156] Step 5: Scanning and quenching.
[0157] Same as Example 1.
[0158] Comparative Example 1 The difference between this comparative example and Example 1 is that the laser spot is a Gaussian circular spot.
[0159] Comparative Example 2 The difference between this comparative example and Example 1 is that a rectangular light spot with a width of 5mm was ultimately selected.
[0160] Comparative Example 3 The difference between this comparative example and Example 1 is that the final laser irradiation angle on the bearing side is determined. Take 55 degrees as the guide side laser irradiation angle. Take 55 degrees.
[0161] Test case The drill pipe joints prepared in the examples and comparative examples were subjected to performance tests. The test items included the uniformity of the hardened layer thickness, the hardening condition of the tooth root, the hardness distribution, the wear resistance, and the impact resistance.
[0162] 1. Hardened layer thickness uniformity test The uniformity of the hardened layer thickness was tested using metallographic microscopy. Samples were cut along the thread axis, mounted, polished, and then etched with a 4% nitric acid-alcohol solution. The boundary between the hardened layer and the substrate was then observed using a metallographic microscope with a magnification of 200×. Five measurement points were selected along the width direction on the bearing side surface of a single tooth (root, 1 / 4, 1 / 2, 3 / 4, and tip of the tooth flank) to measure the hardened layer thickness at each point, and the standard deviation was calculated. A smaller standard deviation indicates a more uniform hardened layer thickness and higher quenching precision.
[0163] 2. Test of the thickness of the hardened layer at the tooth root The root hardened layer thickness test is used to assess whether laser energy spills over into the root arc region of the thread. Metallurgical microscopy is used to observe the presence of martensitic hardened structures in the root arc region of the thread, and the maximum thickness of the root hardened layer is measured. A larger root hardened layer thickness indicates poorer spot size control and a higher risk of root cracking. Ideally, there should be no hardened layer at the root.
[0164] 3. Hardness test Hardness testing was performed using a micro Vickers hardness tester to measure the hardness gradient. The load was set to 300g and the holding time was 10s. Three points were randomly measured in the hardened layer, and the average value was converted to HRC hardness. It should be noted that the original hardness test data in this application were measured using micro Vickers hardness (HV0.3). The main reason is that the total thickness of the hardened layer in this invention is only 0.1mm~0.5mm. If macro Rockwell hardness (HRC) testing were used, the indentation length generated by the 150kgf load would penetrate the entire hardened layer and be affected by the matrix, failing to characterize the true hardness of the hardened layer. Therefore, this application uses a small load Vickers hardness test of 0.3kgf (marked as HV0.3) for layer testing. The obtained HV values were converted to HRC hardness according to general standards.
[0165] Recorded metrics include: Surface hardness on the bearing side: Take the hardness value at a distance of 5μm from the surface on the bearing side; Guide side surface hardness: Take the hardness value at a distance of 5μm from the guide side surface; Five points were randomly selected on each side for measurement, and the average value was converted to HRC hardness.
[0166] 4. Wear resistance test Wear resistance testing employed a ring-block wear test to evaluate the differences in wear resistance caused by different processes. Standard test blocks were cut from samples treated with the same laser quenching process, quenched, and then used for wear resistance testing. Test parameters were set as follows: load 200 N, rotation speed 100 r / min, wear time 30 min, dry friction conditions. The test index was the volumetric wear loss of the test block, measured using a three-dimensional profilometer to measure the wear mark width and calculate the volumetric wear of the test block.
[0167] 5. Impact resistance performance analysis Impact resistance testing employed a drop hammer impact test to assess the toughness of the hardened layer. V-notch specimens were prepared using the load-bearing side of the threaded structure, and impact tests were conducted after hardening. The test parameter was the impact absorbed energy. Three measurements were taken at three points for each specimen, and the average value was recorded. Simultaneously, the fracture morphology was observed to evaluate the fracture mode.
[0168] 6. Test of the number of cycles of upper and lower buckles The thread pull-out cycle test simulates the actual service conditions of the drill pipe joint using a thread pull-out cycle test. The drill pipe joints prepared in the examples and comparative examples were fitted with standard matching joints of the same specifications. The test parameters were set as follows: pull-out torque of 60% of the recommended torque, rotation speed of 10 r / min, and dry friction lubrication (no thread grease applied). The test index was the number of pull-out cycles before sticking failure occurred. Sticking failure was defined as a torque fluctuation exceeding 20% of the initial value or the appearance of obvious scoring marks on the thread surface. Three joints were tested for each sample, and the average value was taken.
[0169] The specific test results are shown in Table 1.
[0170] Table 1
[0171] As can be seen from the test results in Table 1, the drill pipe joint prepared in the embodiment of the present invention is significantly better than the comparative example in terms of uniformity of hardened layer thickness, tooth root safety, hardness matching, wear resistance and impact resistance, which fully verifies the feasibility and superiority of the technical solution of the present invention.
[0172] The standard deviation of the hardened layer thickness in Examples 1-6 is significantly lower than that in Comparative Examples 1-3. This indicates that the present invention effectively achieves a uniform distribution of the hardened layer thickness on a single tooth surface through precise matching of the spot size with the tooth profile, calculation of the irradiation angle formula, and control of energy density. Comparative Example 1 uses a Gaussian circular spot, resulting in a high energy distribution at the center and a low distribution at the edges, leading to a hardened layer that is deep in the middle and shallow at the edges, resulting in poor uniformity. Comparative Example 2 has an excessively large spot size, causing energy overflow and unstable quenching effect at the tooth flank edges. Comparative Example 3 uses a fixed angle, which is not optimized according to the tooth profile parameters, resulting in slight occlusion and energy reflection loss, affecting uniformity.
[0173] In Examples 1-6, the thickness of the hardened layer at the tooth root was 0 mm, indicating that the laser energy precisely covered the working surface of the tooth lateral surface and did not overflow into the arcuate area of the tooth root. In contrast, the hardened layer thickness at the tooth root in Comparative Example 1 was 0.15 mm, in Comparative Example 2 it was as high as 0.55 mm, and in Comparative Example 3 it was 0.25 mm. The presence of a hardened layer at the tooth root leads to the formation of hard and brittle martensite, which is highly susceptible to becoming a crack initiation under alternating loads. In Comparative Example 2, the spot size of 5 mm far exceeded the linear length of the load-bearing side, resulting in severe energy overflow, the largest hardened layer thickness at the tooth root, and the highest risk of tooth root cracking.
[0174] In Examples 1-4 and 6 (using a scanning sequence of first the guide side and then the load-bearing side), the surface hardness of the load-bearing side is slightly higher than that of the guide side. This is because when scanning the load-bearing side, the heat generated by the laser is conducted to the already quenched guide side, producing a self-tempering effect on the guide side, slightly reducing its hardness but significantly improving its toughness. In contrast, in Example 5 (using a scanning sequence of first the load-bearing side and then the guide side), the surface hardness of the guide side is higher than that of the load-bearing side. This is because the heat from the later-scanned guide side tempers the first-scanned load-bearing side, resulting in a decrease in the hardness of the load-bearing side. Although a hardness difference also exists in Example 5, its impact absorption energy is lower than that of Example 1, and the number of buckle-on / off cycles is lower than that of Example 1. This indicates that the preferred first-guide-then-load-bearing sequence of the present invention, which utilizes the heat from the load-bearing side scanning to temper the guide side, can effectively improve the toughness (impact resistance) of the guide side while ensuring high hardness (wear resistance) of the load-bearing side, achieving a match between the performance of both sides.
[0175] Regarding wear resistance, the wear volume loss of the quenched samples in Examples 1-6 was significantly lower than that of the comparative examples. Example 1, using a rectangular laser spot, is designed for high-wear scenarios, resulting in a highly consistent hardened layer depth and superior resistance to severe wear and fatigue. Example 2, using a flat-topped circular laser spot, is designed for low-wear scenarios, exhibiting uniform energy distribution, high process robustness, highly consistent hardened layer structure, and excellent wear resistance stability. Example 3, made of aluminum alloy, has lower hardness and a relatively larger wear volume loss, but it is still superior to all comparative examples. Comparative examples 1-3, due to poor uniformity of the hardened layer or potential defects at the tooth root, showed insufficient wear resistance stability and significantly increased wear volume loss.
[0176] In terms of impact resistance, the impact absorption energy of Examples 1-6 is significantly higher than that of the comparative examples. Example 1, using a rectangular laser spot for high wear scenarios, effectively suppressed fatigue crack propagation with its linear synchronous heating, resulting in the highest impact absorption energy. Example 2, using a flat-topped circular laser spot for low wear scenarios, had the second highest impact absorption energy, verifying the effectiveness of the present invention in selecting the laser spot shape according to the working conditions. Example 5, due to the reversed scanning order, lacked the self-tempering effect on the guide side, leading to a decrease in the synergistic toughness on both sides, resulting in the lowest impact absorption energy among the examples, but still better than all the comparative examples. Comparative Example 1, due to the use of a Gaussian laser spot with uneven energy distribution, had uneven microstructure, resulting in lower toughness. Comparative Example 2, due to its excessively large laser spot size, had a severely hardened layer at the tooth root, becoming a crack source for impact fracture, significantly reducing impact energy. Comparative Example 3, due to inaccurate angle control, had concentrated microstructure and the worst toughness.
[0177] The number of coupling cycles in Examples 1-6 was significantly higher than that in the Comparative Examples. Comparative Examples 1-3 were prone to sticking failure during dry friction coupling due to poor uniformity of the hardened layer, the presence of a hardened layer at the tooth root, or inaccurate angle control.
[0178] This invention achieves high-precision laser quenching of threaded joints by precisely controlling the spot type according to the scene, the spot size to match the tooth profile, and the irradiation angle and energy density calculated by formula. Examples 1-6 demonstrate excellent comprehensive performance under different materials, thread specifications, and process parameters, proving the stability and reliability of the technical solution of this invention. Comparative Examples 1-3 deviate from the solution of this invention in terms of spot type, spot size, and irradiation angle, respectively, resulting in a significant decrease in performance, thus verifying the necessity of the technical features of this invention from the opposite perspective.
[0179] The technical effects of this application will be explained below with reference to specific images.
[0180] Figure 10 This is an optical microscope image of the hardened layer on the bearing side of the threaded joint provided in Embodiment 1 of the present invention. As shown in the figure, after processing with the high-precision laser quenching method of the present invention, the hardened layer (dark area) on the thread flank surface has a uniform thickness and is smoothly distributed along the linear length direction of the bearing side without significant fluctuations. The boundary between the hardened layer and the tempered sorbite structure of the matrix (light area) is clear and the transition is smooth. It is particularly noteworthy that the hardened layer precisely terminates at the arc transition point of the thread root, without extending to the stress concentration area at the root, effectively avoiding the safety hazard of cracks caused by the presence of hard and brittle martensite at the root. This result verifies that the present invention achieves high-precision control of the quenching area by precisely matching the spot size and thread profile parameters, ensuring the wear resistance and structural safety of the thread mating surface.
[0181] Figure 11 This is an optical microscope image of the hardened layer on the bearing side of the threaded joint provided in Comparative Example 1 of the present invention. As shown in the figure, after processing with traditional laser quenching technology, the hardened layer thickness distribution on the thread tooth flank surface is uneven, exhibiting a thicker center and thinner edges. This will lead to inconsistent wear on the thread mating surface and reduce the service life of the joint. This result reflects the problems of uneven hardened layer quality and poor safety caused by low spot size and tooth profile matching and coarse process parameter control in the prior art.
[0182] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A high-precision laser quenching method for threaded joints, characterized in that, Includes the following steps: The shape of the laser spot is determined based on the application scenario of the threaded joint; Based on the thread profile parameters of the threaded connector, determine the size of the laser spot and the irradiation angle of the laser beam; The laser power and scanning speed for laser quenching are determined based on the properties of the joint material. Using the determined laser spot, irradiation angle, laser power, and scanning speed, the laser beam is used to scan and quench the guide side and load-bearing side of the threaded joint to form a hardened layer.
2. The laser quenching method according to claim 1, characterized in that, The application scenarios of the threaded joint include low-wear scenarios and high-wear scenarios; if the application scenario is a low-wear scenario, the laser spot is determined to be a flat-topped circular spot; if the application scenario is a high-wear scenario, the laser spot is determined to be a rectangular spot.
3. The laser quenching method according to claim 2, characterized in that, Determining the size of the laser spot specifically includes: Calculate the linear length of the bearing side of the thread tooth based on the thread profile parameters of the threaded joint; When the laser spot is determined to be a flat-topped circular spot, the diameter of the flat-topped circular spot is 85% to 115% of the linear length of the bearing side; Alternatively, when the laser spot is determined to be a rectangular spot, the width of the rectangular spot is 85% to 115% of the linear length of the bearing side.
4. The laser quenching method according to claim 1, characterized in that, Determining the illumination angle of the laser beam includes: The angle between the central axis of the laser beam and the axis of the threaded joint is determined to be 30°~70°; The illumination angle includes a guide side illumination angle and a load-bearing side illumination angle, and the guide side illumination angle and the load-bearing side illumination angle are determined independently. The illumination angle on the bearing side and the illumination angle on the guide side are both the angle between the laser beam and the axis of the threaded joint; The formula for calculating the irradiation angle on the bearing side is: in, For the irradiation angle on the bearing side, The linear length of the thread tooth on the bearing side. The radius of the tooth root arc, It is a tooth-shaped half-angle; The formula for calculating the guide side illumination angle is: in, For the guide side illumination angle, The linear length of the thread guide side. The radius of the tooth root arc, It is a tooth-shaped half-angle; The formula for calculating the linear length of the thread tooth bearing side is: in, The linear length of the thread tooth on the bearing side. The height of the tooth profile. The radius of the tooth root arc, The taper of the threaded connector. It is a tooth-shaped half-angle.
5. The laser quenching method according to claim 4, characterized in that, The formula for calculating the linear length of the thread guide side is: in, The linear length of the thread guide side. The height of the tooth profile. The radius of the tooth root arc, The taper of the threaded connector. It is a tooth-shaped half-angle.
6. The laser quenching method according to claim 4, characterized in that, The illumination angle on the guide side and the illumination angle on the bearing side are also independently compensated, with the range of angle compensation being 0°~10°.
7. The laser quenching method according to claim 1, characterized in that, The process of determining the laser power and scanning speed for laser quenching based on the properties of the joint material includes: When the connector material is medium carbon alloy steel, the laser power is 300W~2000W and the scanning speed is 10mm / s~60mm / s; When the connector material is aluminum alloy, the laser power is 300W~1000W and the scanning speed is 2mm / s~10mm / s.
8. The laser quenching method according to claim 3, characterized in that, The laser power and scanning speed satisfy the following energy density relationship: in, The critical energy density of the joint material is 15 J / mm². 2 ~60J / mm 2 ; Laser power; For scanning speed; It represents the diameter of a flat-topped circular light spot or the width of a rectangular light spot.
9. The laser quenching method according to claim 1, characterized in that, The guide and load-bearing sides of the threaded joint are scanned and quenched using a laser beam, specifically including: First, the guide side of the threaded joint is subjected to laser hardening scanning; After completing the quenching scan on the guide side, the bearing side of the threaded joint is then subjected to laser quenching scan. In the laser quenching process, the scanning direction is always from the large end to the small end of the threaded joint, where the laser beam moves to scan.
10. A threaded connector, characterized in that, It is processed by the laser quenching method as described in any one of claims 1 to 9.
